Effects of Co-Doped Bimetallic Impurities on the Growth and Nucleation Kinetics of Potassium Acid Phthalate (KAP) - Begum, SA; Podder, J (Journal of Bangladesh Academy of Sciences, 2010)
Single crystals of pure potassium acid phthalate (KAP) and nickel-magnesium (Ni-Mg), cobalt-magnesium (Co2+-Mg2+) and lithium-magnesium (Li1+-Mg2+) co-doped potassium acid phthalate crystals were grown by an isothermal evaporation method. Good quality and optically transparent single crystals of pure and bimetallic doped KAP were grown. Enhancement of the metastable zonewidth was achieved by the addition of co-doped novel bimetallic impurities in KAP solution. The induction period and various critical nucleation parameters such as radius of critical nucleus, number of molecules in the critical nuclei and the critical free energy change were calculated based on the classical theory for homogeneous nucleation. The induction period decreases exponentially with supersaturation ratio and hence the nucleation rate increases with the increase of supersaturation ratio for all systems. Subsequent incorporation of these bimetallic co-doped impurities into the crystal would allow the growth rate to achieve its maximum value. The induction period is found to increase with the incorporation of Ni2+, Co2+and Li1+ ions doped along with Mg2+ ions in KAP. It is anticipated that these larger cations play a vital role in the growth mechanism and it favors to reduce the formation of secondary nucleation by positioning the doped metal ions into the interstitial sites. DOI: 10.3329/jbas.v33i2.4102 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 189-197, 2009